EFL TEACHERS’ COGNITION OF EMERGENCY REMOTE INSTRUCTIONS - Paulus Widiatmoko (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research investigated how EFL teachers made sense of online instruction during Covid19 pandemic to facilitate English language skill development. Taking a college English matriculation program as the context of the study, nine excerpts of teacher term reflections were analysed using critical incident analysis. Five cluster of incidents were identified essential to represent the landscape of the EFL teachers’ cognition of distance instruction. They were teachers’ adjustments and renewal of pedagogic practice, representation of belief system, enactment of technological pedagogical content knowledge (TPCK), involvement of their emotion, and acceptance of the abrupt changes. These themes asociated with readiness for online instruction as it was not only related to physical-technical issues, but also concerned with more intricate realm of technology integration for online learning